2020
DOI: 10.1111/nph.16599
|View full text |Cite
|
Sign up to set email alerts
|

Two receptor‐like protein kinases, MUSTACHES and MUSTACHES‐LIKE, regulate lateral root development in Arabidopsis thaliana

Abstract: Receptor-like protein kinases (RLKs) play key roles in regulating plant growth, development and stress adaptations. There are at least 610 RLKs (including receptor-like cytoplasmic kinases) in Arabidopsis. The functions of the majority of RLKs have not yet been determined. We previously generated promoter::GUS transgenic plants for all leucine-rich repeat (LRR)-RLKs in Arabidopsis and analyzed their expression patterns during various developmental stages. We found the expression of two LRR-RLKs, MUSTACHES (MUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Furthermore, BR‐SIGNALING KINASE 1 (BSK1), a critical RLCK in the BR pathway, can positively regulate flg22‐triggered immune response by associating with the FLS2 complex and subsequently activating MAPK cascade by phosphorylation (Figure 4) (Yan et al, 2018). In addition to BSK1, other members of the BSK subfamily also regulate plant immunity.…”
Section: Regulation Of Rlks and Rlpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BR‐SIGNALING KINASE 1 (BSK1), a critical RLCK in the BR pathway, can positively regulate flg22‐triggered immune response by associating with the FLS2 complex and subsequently activating MAPK cascade by phosphorylation (Figure 4) (Yan et al, 2018). In addition to BSK1, other members of the BSK subfamily also regulate plant immunity.…”
Section: Regulation Of Rlks and Rlpsmentioning
confidence: 99%
“…For instance, the Arabidopsis STRUBBELIG (SUB) receptor is involved in tissue morphogenesis and controls the composition of the plant cell wall (Chaudhary et al, 2020). Meanwhile, the kinase-inactive RLKs MUS-TACHES (MUS) and MUSTACHES-LIKE (MUL) can control lateral root development (Xun et al, 2020). Although MUS and MUL are in vitro kinase-inactive RLKs, they are phosphorylated by an unidentified kinase in planta (Xun et al, 2020).…”
Section: Lrr-rlks In Plant Growth and Developmentmentioning
confidence: 99%
“…FERONIA (FER) functions as the receptor of peptide Rapid Alkalinization Factor 1 (RALF1) to regulate root growth, which may be related to endocytosis of plasma membrane proteins [ 170 , 171 ]. MUSTACHES (MUS) and MUSTACHES-LIKE (MUL), two LRR-RLKs, modulate lateral root primordial development by controlling the biosynthesis and remodeling of the cell wall [ 172 ]. However, there is no evidence yet that these RLKs regulate root development through MAPK cascades.…”
Section: Rlks and Mapk Cascades Regulate Root Developmentmentioning
confidence: 99%
“…Moreover, we found that some TFs, up-regulated in SS compared with those in TS, are related to various processes of the late phases of wood formation. For example, miR6425-x CTG ARF7 (Potri.006G077800) indirectly regulates cell wall synthesis and remodelling by activating MUS and MUL, two kinase-inactive RLKs, under auxin [48]. MYB23 (Potri.001G169600), a CTG of miR3946-x, is a homologous gene of MYB52 and plays roles in regulating cuticle biosynthetic pathways [42].…”
Section: Functions Of De-mirnas In Diverse Phases Of Wood Formationmentioning
confidence: 99%
“…x was found to be involved in the late phase of wood formation by signi cantly alleviating the inhibitory effects on the target TF ARF7 (Potri.006G077800) ( Fig. 9), which activates cell wall synthesis and remodelling processes [48], in SS compared with those in PS. Most notably, we found that miR384-x regulated SHN2 (Potri.018G028000 and Potri.006G253800), which is a high hierarchical master switch TF that appears to control the switch between cellulose and lignin biosynthesis [45], suggesting that miR384-x participates in multiple biological processes, such as secondary wall biosynthesis, ligni cation, and PCD, of the middle and late phases of wood formation (Fig.…”
Section: Functions Of the Rst Identi Ed Mirnas Participate In Diversementioning
confidence: 99%